Associations of polysocial risk score with incident rosacea: a prospective cohort study of government employees in China - Peng Chen; Ziye Yang; Zhihua Fan; Ben Wang; Yan Tang; Yan Tang; Yan Tang; Yi Xiao; Xiang Chen; Xiang Chen; Dan Luo; Shuiyuan Xiao; et al. (Frontiers Media S.A., 2023)
BackgroundThe associations between single risk factors and incident rosacea have been reported, but the effects of social risk factors from multiple domains coupled remain less studied.ObjectivesTo quantify the influence of social determinants on rosacea comprehensively and investigate associations between the polysocial risk score (PsRS) with the risks of incident rosacea.MethodsThis was a prospective cohort study of government employees undertaken from January 2018 to December 2021 among participants aged >20 from five cities in Hunan province of China. At baseline, information was collected by a questionnaire and participants were involved in an examination of the skin. Dermatologists with certification confirmed the diagnosis of rosacea. The skin health status of participants was reassessed every year since the enrolment of study during the follow-up period. The PsRS was determined using the nine social determinants of health from three social risk domains (namely socioeconomic status, psychosocial factors, and living environment). Incident rosacea was estimated using binary logistic regression models adjusted for possible confounding variables.ResultsAmong the 3,773 participants who completed at least two consecutive skin examinations, there were 2,993 participants included in the primary analyses. With 7,457 person-years of total follow-up, we detected 69 incident rosacea cases. After adjustment for major confounders, participants in the group with high social risk had significantly raised risks of incident rosacea with the adjusted odds ratio (aOR) being 2.42 (95% CI 1.06, 5.55), compared to those in low social risk group.ConclusionOur findings suggest that a higher PsRS was associated with an elevated risk of incident rosacea in our study population.